2022
DOI: 10.3389/fcell.2021.792257
|View full text |Cite
|
Sign up to set email alerts
|

Harmine Alleviated Sepsis-Induced Cardiac Dysfunction by Modulating Macrophage Polarization via the STAT/MAPK/NF-κB Pathway

Abstract: Sepsis is a dysregulated systemic inflammatory response that often leads to cardiac dysfunction, which is termed sepsis-induced cardiomyopathy (SIC). Harmine, a natural β-carboline alkaloid compound, has been shown to exert pharmacological effects on several diseases. Here, we investigated whether harmine protected against SIC development and the underlying mechanisms. In vitro, the expression of the M1 phenotype markers iNOS and COX-2 was increased in RAW 264.7 cells stimulated with lipopolysaccharide (LPS), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…The MAPK/NF-κB/STAT pathway plays a crucial role in macrophages, which can be affected by a variety of factors to change their phenotype and, thus, affect their function [ 15 , 16 , 19 , 33 ]. In line with previous reports [ 34 , 35 , 36 ], LPS + IFN-γ treatment significantly resulted in phosphorylation of ERK, p38, JNK, p50 and p65 ( Figure 6 A,C), and IL-4 treatment led to phosphorylation of Akt, STAT3 and STAT6 in THP-1 ( Figure 7 A), demonstrating the activation of the MAPK-NF-κB pathway or the Akt/STAT pathway in M1 or M2 macrophage polarization, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The MAPK/NF-κB/STAT pathway plays a crucial role in macrophages, which can be affected by a variety of factors to change their phenotype and, thus, affect their function [ 15 , 16 , 19 , 33 ]. In line with previous reports [ 34 , 35 , 36 ], LPS + IFN-γ treatment significantly resulted in phosphorylation of ERK, p38, JNK, p50 and p65 ( Figure 6 A,C), and IL-4 treatment led to phosphorylation of Akt, STAT3 and STAT6 in THP-1 ( Figure 7 A), demonstrating the activation of the MAPK-NF-κB pathway or the Akt/STAT pathway in M1 or M2 macrophage polarization, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that complete polarization of macrophages to the M1 type requires activation of the MAPK and NF-κB signaling pathways [ 19 , 27 , 31 , 61 ], and M2 macrophage polarization requires activation of the STAT signaling pathway [ 62 , 63 ]. To explore the signal transduction pathways underlying the regulatory effects of TcpC on M1/M2 polarization, the influence of TcpC on MAPK/NF-κB and Akt/STAT pathways was examined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Western blot analysis was performed as previously described [ 15 ].Total protein was extracted from myocardial tissues using lysis buffer (Sigma-Aldrich, MD, USA). Proteins were separated on 10% SDS-PAGE and then transferred onto polyvinylidene fluoride (PVDF) membranes.…”
Section: Methodsmentioning
confidence: 99%
“…To mimic the crosstalk between macrophages and cardiomyocytes, different co-culture models are commonly utilized [ 24 , 25 , 26 ]. However, due to the fact that cardiomyocytes are directly or indirectly exposed to conditioned medium of proinflammatory macrophages containing cytokines, growth factors, hormones, eRNA, and EVs, the underlying pathomechanisms are highly complex and require further studies [ 17 , 27 ].…”
Section: Introductionmentioning
confidence: 99%